Non-Ownership and the Commons: Access and Exclusion in the Life of Communities - Quarta, Alessandra (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2020)
This article introduces the category of the commons and presents the main findings of our research into this concept in the Italian legal system. The commons are based on the principle of access and for this reason, they challenge the traditional rules of property law where the right to exclude has a pivotal role.This paper will analyze the centrality of the system for the management of the commons, the relationships between the nature of assets and the organization of human groups. Our starting point is the presumptive necessity to redefine the interplay between property (more precisely, non-ownership) and community.